Ukraine : Technical Assistance Report. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Assistance Report discusses measures to enhance the powers and independence of the National Securities and Stock Market Commission (NSSMC) in Ukraine. The NSSMC faces significant challenges in its role as the regulator of the Ukrainian securities market. Market activity has been shrinking over the past few years, but misconduct-such as issuance and trading of 'fictitious' securities-prevails. Key changes needed relate to enhancing the NSSMC's ability to conduct investigations of and demand information from any legal or natural person, have access to information otherwise restricted by secrecy laws, assist foreign authorities even without an apparent violation of the Ukrainian securities laws, and maintain the confidentiality of information exchanged under the Multilateral Memorandum of Understanding.